Hasselblatt, Cornelius – Houtzagers, Peter – van Pareren, Remco (eds.): Language contact in times of globalization - Saarinen, Sirkka (Finnisch-Ugrische Forschungen, 2012)
Cornelius Hasselblatt, Peter Houtzagers & Remco van Pareren (eds.), Language contact in times of globalization. (Studies in Slavic and general linguistics, vol. 38.) Amsterdam – New York: Rodopi, 2011. 287 pp